Sosialisasi Literasi Keuangan Syariah Pada Masyarakat RT. 28 Kelurahan Kenali Asam Bawah Jambi - Nova Erliyana; Rabiyatul Alawiyah (Literasi Nusantara Publisher, 2022)
Indonesia is a country with a majority Muslim population. The lack of socialization of Islamic financial literacy means that people do not yet know and realize the importance of Islamic financial institutions in economic activities by Islamic principles to achieve falah, namely the welfare of the world and the hereafter. This activity aims to increase the understanding of RT study members. 28 Kenali Asam Bawah Village, Kota Baru District, Jambi City regarding Islamic financial literacy. This community service activity starts with planning, implementation and evaluation. The results of the socialization of Islamic financial literacy activities show that socialization participants have an increased understanding of Islamic finance.